First Report of Root Rot in Aralia elata Caused by Phytophthora cactorum in China - Zheng, Zeyang (Plant disease, 2024)
Aralia elata (Miq.) Seem, is an important cash crop in northeastern China. The tender shoots are rich in amino acids, vitamins, and trace elements, and the saponins of leaves and roots have antioxidant and immune-boosting properties. In August of 2023, root rot disease was observed in 4-year-old A. elata plants in Dongzhou County (41.79 °N, 124.11 °E), Liaoning Province, China, with an overall incidence of approximately 40%. While previous studies have described root rot in A. elata caused by Fusarium oxysporum (Zheng et al. 2024), this new root rot showed different symptoms. The leaves of the diseased plants were water-soaked and wilted but not chlorotic. The internal tissue of the roots was disintegrated and soft, while the xylem appeared brown and empty with only the epidermis remaining. Diseased root tissues were sterilized with 75% ethanol for 30 s, treated with 2% sodium hypochlorite for 2 min, and rinsed twice in sterile distilled water. Twelve isolates with similar morphological characteristics were obtained (isolation frequency of 80%), the isolates were plated on PDA medium and incubated at 25℃. Single-zoospore cultures were obtained and transferred to soybean agar medium (SA). After growth on SA for 7 days, the formation of rounded colonies of white aerial mycelia was observed. The sporangia were ovoid or ellipsoid, papillate, terminally borne, with an average length and width of 30.24 (18.35 to 45.39) × 24.16 (14.55 to 37.64) μm. The isolates were homothallic, produced plerotic oogonia with smooth walls with an average diameter of 27.97 (21.06 to 35.90 μm), and yielded one paragynous or anohiginous antheridium, sized 12.21 (10.11 to 14.72) μm × 9.75 (8.39 to 11.31) μm. Based on these morphological characteristics, the isolates were identified as part of the Phytophthora genus (Montealegre et al. 2016). The internal transcribed spacer (ITS) region and cytochrome oxidase subunit Ⅱ (COXⅡ) gene were amplified using the respective primers ITS1/ITS4 and FM66/FM58 (Wiseman et al. 2018). The ITS and COXⅡ sequences were compared with sequences in GenBank, showing 99.83% to 100% sequence identity with Phytophthora cactorum (accession nos. OR347848 and OR351295, respectively). The sequences have been deposited in GenBank with the accession numbers PP479774 (ITS) and PP489221 (COXⅡ). Construction of a maximum-likelihood phylogenetic tree of the identified sequences using MEGA-X indicated that the isolate could be identified as P. cactorum. To confirm pathogenicity, shallow wounds were made in the taproots of 10 one-year-old A. elata and were inoculated with four 9-mm diameter agar plugs from one-week-old oomycete cultures on SA agar per root, and the pathogenicity test was repeated twice. Another 10 wounded plants inoculated with agar plugs without oomycete served as the controls. The plants were planted in flowerpots filled with sterilized forest soil and cultured in a greenhouse at 25℃ with 14 h of light per day. After 20 days, the inoculated plants showed similar symptoms to those initially observed in the field. No symptoms of root rot were observed in the controls. The P. cactorum was re-isolated from the inoculated plants, and identified based on the morphology and ITS and COXⅡ sequence, fulfilling Koch's postulates. P. cactorum has been reported to cause root rot in A. elata in Korea and Japan (Lee et al. 2005; Uchida et al. 1984). To our knowledge, this is the first report of P. cactorum causing root rot in A. elata in China. P. cactorum is a serious threat to A. elata cultivation, and disease management strategies need to be developed